AMMONIUM TRANSFORMATION IN A NITROGEN-RICH TIDAL FRESHWATER MARSH - Gribsholt B.; Struyf E.; Tramper A.; Andersson M.G.I.; Brion N.; De brabandere L.; Van damme S.; Meire P.; Middelburg Ja.J.; Dehairs F.; Boschker H.T.S. (My University, 2006)
The fate and transport of watershed-derived ammonium in a tidal freshwater marsh fringing the nutrient rich Scheldt River, Belgium, was quantified in a whole ecosystem 15N labeling experiment. In late summer (September) we added 15N-NH 4 + to the flood water entering a 3477 m2 tidal freshwater marsh area, and traced the ammonium processing and retention in four subsequent tide cycles. In this paper we present the results for the water-phase components of the marsh system and compare them to a similar experiment conducted in spring/early summer (May). Changes in concentration and isotopic enrichment of NO 3 −  + NO 2 − , N2O, N2, NH 4 + and suspended particulate nitrogen (SPN) were measured in concert with a mass balance study. All analyzed N-pools were labeled, and 49% of the added 15NH 4 + was retained or transformed. The most important pool for 15N was nitrate, accounting for 17% of 15N-transformation. N2, N2O and SPN accounted for 2.4, 0.02 and 1.4%, respectively. The temporal and spatial patterns of 15N transformation in the water phase component of the system were remarkably similar to those observed in May, indicating good reproducibility of the whole ecosystem labeling approach, but the absolute ammonium transformation rate was 3 times higher in May. While the marsh surface area was crucial for nitrification in May this was less pronounced in September. Denitrification, on the other hand, appeared more important in September compared to May.
Keywords: NITROGEN TRANSFORMATION; TIDAL FRESHWATER MARSH; 15N; NITRIFICATION; DENITRIFICATION